Key populations and healthcare providers perceptions, preferences and acceptability of HIV, Hepatitis B and C multiplex self-testing: A qualitative study - Elena Marbán-Castro; Caroline Thomas; Danil Nikitin; Catherine Thomas; Alla Bessonova; Sergei Bessonov; Claudius Mone Iye; Aibek Bekbolotov; Maia Japaridze; Mikaela Watson; Elena Ivanova; Olga Denisiuk; et al. (PLoS ONE, 2026)
Human immunodeficiency virus (HIV), hepatitis B virus (HBV), and hepatitis C virus (HCV) are chronic viral infections, sharing similar transmission routes. This study investigates the perceptions, preferences and acceptability of people who inject drugs (PWID) and healthcare providers (HCP) on multiplex rapid diagnostic tests (RDT) intended for self-testing (ST) for HIV, HBV and HCV. This was a qualitative study conducted in Indonesia and Kyrgyzstan. This study employed focus group discussions (FGDs) and semi-structured interviews (SSIs) to obtain general perceptions and theoretical acceptability on multiplex ST and cognitive interviews to optimize instructions for use (IFU). The IFU used were from four different manufacturers: PMC dual (HIV/HCV) ST in Kyrgyzstan, Mylab triple (HIV/HCV/HBV) ST in Kyrgyzstan, BioLytical (HIV/HCV), dual ST in Indonesia and Bioera Triple (HIV/HCV/HBV) ST in Indonesia. Eleven SSIs and twelve FGDs were conducted across both countries. A total of 110 participants were included in SSI and FGD: five stakeholders, 27 PWID, and 24 HCP in Kyrgyzstan and six stakeholders, 24 PWID, and 24 HCP in Indonesia. Participants reported the main factors that would facilitate the use of multiplex ST 1) quick time to results, 2) easy to use, 3) affordability, 4) confidentiality, and 5) ability to diagnose several infections at once. A total of 118 participants were included in cognitive interviews. Cognitive interviews led to recommendations for improving IFU, including larger fonts and simplified language. This study demonstrates initial acceptability of multiplex ST for HIV/HCV/HBV among PWID, HCP, and stakeholders. Still, communication strategies, tailored IFU, targeted training to HCP and counseling to PWID are needed for future implementation.